2019
DOI: 10.1136/bmjgast-2019-000322
|View full text |Cite
|
Sign up to set email alerts
|

Associations of chronic diarrhoea with non-alcoholic fatty liver disease and obesity-related disorders among US adults

Abstract: Mechanisms explaining observed associations between diarrhoea and obesity or increased body mass index (BMI) are unclear.ObjectiveTo assess associations of bowel patterns with BMI, metabolic syndrome (MS), non-alcoholic fatty liver disease (NAFLD) and other obesity-related disorders.DesignWe performed a cross-sectional analysis of data from adults who completed bowel health questions for the 2005 to 2010 cycles of the National Health and Nutrition Examination Surveys. Relationships were examined using multinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Similar result was reported in a National Health and Nutrition Examination Survey among US adults, found positive association between obesity and chronic diarrhoea. 34 A birth cohort study conducted among 980 young adults in Dunedin, New Zealand, also found positive association between increased BMI and diarrhoea. 35 Literature also suggests that up to 8.5 per cent of obese and 11.5 per cent of severely obese individuals had chronic diarrhoea, compared with 4.5 per cent of normal-weight individuals.…”
Section: Discussionmentioning
confidence: 96%
“…Similar result was reported in a National Health and Nutrition Examination Survey among US adults, found positive association between obesity and chronic diarrhoea. 34 A birth cohort study conducted among 980 young adults in Dunedin, New Zealand, also found positive association between increased BMI and diarrhoea. 35 Literature also suggests that up to 8.5 per cent of obese and 11.5 per cent of severely obese individuals had chronic diarrhoea, compared with 4.5 per cent of normal-weight individuals.…”
Section: Discussionmentioning
confidence: 96%
“…55 Interestingly, the relationship between R. gnavus and IBS lost its significant in adjusted analyses due to a positive association between R. gnavus and BMI which may suggest a role R. gnavus in explaining the connection between IBS-D or chronic diarrhea with metabolic syndrome and obesity-related disorders. 56, 57 Associations of IBS-D with other taxa including Dorea sp. CAG:317, Blautia sp.…”
Section: Discussionmentioning
confidence: 99%
“…Shin et al [ 16 ] found that the prevalence of presumed NAFLD was 12.9% in patients with diarrhoea predominant IBS (IBS-D) compared to 9.0% in patients with constipation predominant IBS (IBS-C), although the reasons for this apparent difference are unclear and merit further investigation. In an interesting study by Lee et al [ 19 ], rather than evaluating patients with a formal diagnosis of NAFLD, the authors assessed the incidence of elevated liver transaminases and the metabolic syndrome in patients with IBS, compared to an age and sex matched control group.…”
Section: The Prevalence Of Co-existing Ibs and Nafldmentioning
confidence: 99%